Aerodynamic external pressure loads on a semi-circular bluff body under wind gusts. (April 2015) - Chevula, Sreenadh; Sanz-Andres, Angel; Franchini, Sebastián
Abstract: This brief communication concerns the unsteady aerodynamic external pressure loads acting on a semi-circular bluff body lying on a floor under wind gusts and describes the theoretical model, experimental setup, and experimental results obtained. The experimental setup is based on an open circuit, closed test section, low speed wind tunnel, which includes a sinusoidal gust generating mechanism, designed and built at the Instituto de Microgravedad "Ignacio Da Riva" of the Universidad Politécnica de Madrid (IDR/UPM). Based on the potential flow theory, a theoretical model has been proposed to analyse the problem, and experimental tests have been performed to study the unsteady aerodynamic loads on a semi-circular bluff body. By fitting the theoretical model predictions with the experimental results, influencing parameters of the unsteady aerodynamic loads are ascertained. The values of these parameters can help in clarifying the phenomenon of the external pressure loads on semi-circular bluff body under various gust frequencies. The theoretical model proposed allows the pressure variation to be split into two contributions, a quasi-steady term and an unsteady term with a simple physical meaning. Highlights: Unsteady aerodynamic loads acting on bluff bodies have been investigated. A theoretical model has been proposed to analyze these unsteady loads. A new stagnation-pressure referenced coefficient has been proposed. Contribution of the steady & unsteady flows on the final loads have been analysed. Unsteady flow terms are in quadrature with the quasi-steady term.